Contact with primary care physicians among adults with pre-existing common mental health problems during the COVID-19 pandemic: a registry-based study from Norway - Pia Jensen; Christian Madsen; Lars Johan Hauge; Kristin Gustavson; Ingunn Olea Lund; Johanne Hagen Pettersen; Ann Kristin Skrindo Knudsen; Anne Reneflot; Ragnhild Eek Brandlistuen; Unnur Anna Valdimarsdóttir; Helga Ask; Ragnar Nesvåg (BMC, 2023)
Abstract Background During the COVID-19 pandemic, individuals with pre-existing mental health problems may have experienced additional stress, which could worsen symptoms or trigger relapse. Thus, this study aimed to investigate if the number of consultations with general practitioners (GPs) among individuals with a pre-existing common mental health problem during the pandemic differed from pre-pandemic years. Methods Data on consultations with GPs among 18-65-year-olds registered with common mental health problems in 2017-2021 were retrieved from the Norwegian Control and Payment of Health Reimbursements Database. Based on data from the pre-pandemic years (2017-2019), we predicted the number of consultations per week for depression, anxiety disorder, phobia/obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), and eating disorders during the pandemic (March 2020-December 2021) among individuals with pre-existing mental health problems. The forecasted and observed trends in GP consultations per week during the pandemic were stratified by diagnosis, gender, and age groups. Results The observed number of consultations for anxiety disorder, PTSD, and eating disorders were significantly higher than forecasted during extended periods of the two pandemic years. The differences were largest for PTSD (on average 37% higher in men and 47% higher in women during the pandemic), and for eating disorders among women (on average 87% higher during the pandemic). There were only minor differences between the predicted and observed number of consultations for depression and phobia/OCD. Conclusions During the pandemic, individuals with a recent history of mental health problems were more likely to seek help for anxiety disorder, PTSD, and eating disorders, as compared to pre-pandemic years.